Technical Tools and Technologies Used in Distance Education - Shohista Rustamova (Euro Asian Journal Publishing, 2023)
This article provides information about the technical tools and technologies used in distance education, the necessary factors for the effectiveness of distance education.
Keywords: distance education; tools; technologies